KONSEP STRATEGI DALAM MENEGAKKAN HAK BERDAULAT DI LAUT NATUNA UTARA - Mardiyah, Shoim; Hifni, Mucha; Kusman, Asep; Pratowo , Alim Bimo (JURNAL MAHATVAVIRYA, 2023)
Indonesia as a maritime country with a wealth of islands spread over more than 17 thousand islands holds various potentials and opportunities for the progress of the nation. In Indonesia's geostrategic perspective, the sea is seen as a unifier of separate islands. On the other hand, such a vast sea also holds challenges and even triggers threats to the sovereignty of the Indonesian nation itself. The purpose of the research is to find out the potential wealth of Indonesia and realize the government's geostrategy that can be done regarding the North Natuna Sea region. The research method uses qualitative descriptions with literature studies. Maintaining the sovereignty of the Republic of Indonesia on land, sea and air is a mandate that needs to be fought as well as possible. Especially the condition of Indonesia as an archipelagic country that aspires to become the world's maritime axis, of course, must be able to show the welfare of its own people by independently utilizing the natural products in it. In addition to welfare, of course, a sense of security to take and manage natural products needs to be realized. the government must take action through strategies that can be taken either through the political, social or technological fields. The goal is not only to strengthen sovereignty over the territory that is our right and obligation to protect it, but of course there is a shared responsibility to create a sense of security for Natuna fishermen in sailing.